Molecular and morphological analyses revealed a cryptic species of dojo loach Misgurnus anguillicaudatus (Cypriniformes: Cobitidae) in Japan. Issue 3 (September 2017) - Okada, R.; Inui, T.; Iguchi, Y.; Kitagawa, T.; Takata, K.; Kitagawa, T.
Abstract : Although it has been reported that populations of the Japanese dojo loach Misgurnus anguillicaudatus (Cypriniformes: Cobitidae) belong to two distinct mitochondrial (mt)DNA (Type I and Type II), the taxonomic status of the species remains unresolved. To address this question, nuclear DNA and morphological analyses were performed on M. anguillicaudatus population in the Nakaikemi Wetland, where Type I and Type II lineages are sympatric. Results suggest the existence of a cryptic species (Type I) within the Japanese dojo loach.